PENGARUH PROFITABILITAS, TINGKAT SUKU BUNGA DAN NILAI TUKAR TERHADAP INDEKS HARGA SAHAM PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA (TAHUN 2010-2014) - Lusiana, Lusiana; Zein, Febri Randy; Meri, Mufrida (Jurnal Ekobistek, 2016)
This study aims to determine the effect of profitability, Interest Rate and Exchange Rate Against Stock Price Index of Manufacturing Companies Listed on the Indonesian Stock Exchange. At this research variables are variables ditliti profitability, interest rate and exchange rate as independent variables and the stock price index of manufacturing as the dependent variable. Data collection techniques used in this study is the method of documentation. The analytical method used is descriptive method, multiple regression analysis, determination coefficient analysis, t test and f. On the results, a) variable profitability effect positive and significant on the stock price index of manufacturing, evidenced by the t value 8.387> t table 2.00 with a significant level of 0.000 <00.5. b) variable interest rate effect negative and not significantly on the stock price index of manufacturing, evidenced by the t value -1.138 <t table 2.00 with a significant level of 0.260> 0.05. c) and variable exchange rate effect positive and significantly on the stock price index of manufacturing, evidenced by the t value 3.387> t table 2.00 with a significant level of 0.001 <0.05. d) Variable profitability, interest rates and exchange rates affect the stock price index of manufacturing, evidenced by the value of 81.157 f count> f table with a significant level of 2.77 0.000 <0.05. Based on the test results of the coefficient of determination, the variable profitability, interest rate and exchange rate gives a contribution of 80.3% of the stock price index of manufacturing. While the remaining 18.7% is influenced by other variables not examined in this study. Finally the authors suggest to the government to be able to be wise in controlling the macro-economic conditions in order to create a stable macroeconomic conditions and better in the future. As well, the investor can choose investment products more profitable. Keywords : Profitability, Interest Rates, Exchange Rates, Stock Price Index in Manufacturing  Sector.